Romanian aspectual verbs: Restructuring and functional heads - Elena Lăcătuș (Bucharest Working Papers in Linguistics, 2017)
The present paper evaluates Fukuda’s (2007a, 2008) Functional Head Analysis of aspectual verbs on the basis of the analysis of aspectual verbs in Romanian with focus on whether they induce restructuring, whether they occupy functional projections, and whether the structural position which they occupy is reflected in their control and/or raising behaviour. The data indicates that Romanian aspectual verbs behave like lexical verbs. They merge in the same syntactic position, irrespective of the complement which they select and which can be uniformly analysed as ModP/FinP. Their control or raising behaviour is not correlated with different syntactic positions.